SOCIAL REPORT AS A TOOL OF DIALOGUE WITH SOCIET - SHAPOVAL, G.; KOSIAK, A. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The purpose of this article is to determine the reasons that determine the need for social reporting, analysis of international experience in compiling social reports, identify the main components of social reporting from the standpoint of meeting the information needs of stakeholders and the main stages of its preparation. The paper identifies the reasons that determine the need for social reporting, analyzes the international experience of social reporting, identifies the main components of social reporting from the standpoint of meeting the information needs of stakeholders and the main stages of its preparation. As for the enterprises of Ukraine, taking into account the specifics of the business environment of their activities, the structure of their social report may include the following sections: 1) Information about the company. This section provides information about the mission and values of the company, the main results of work, information on risk management of the enterprise, information about stakeholders and ways to interact with them. 2) Economics. It provides information on the impact of the company on the economy of the region and the country as a whole, importance for society, characteristics and prospects for improving the quality of services, cooperation with universities to improve the knowledge of graduates and promote education and business. 3) Society. This section may include 2 components - external and internal. Internal is concern for staff, external is concern for society. 4) Environment. This section provides information on energy efficiency and eco-practices in the company’s offices. In particular, information on energy and water consumption in the company’s offices, the use of the principles of "green office" in the work of the enterprise, the use of electronic document management. 5) Anti-corruption activities. Given the great relevance of this topic for the economy of Ukraine, it is advisable to include this section in the report on social responsibility to inform the public about the activities of the company in the direction of anti-corruption policy. Thus, in the process of preparing social reporting to establish an effective policy of interaction with stakeholders, openness and open dialogue on performance, priorities and future plans related to sustainable development are the only effective way to establish mutually beneficial partnerships and the ability to ensure their own competitive advantage.